Calendars and ecosystem management: Some observations - Francis, Merlin (2015)
Indigenous cultures evolve in relation to available natural resources that can be managed to provide livelihoods, both in temporal and spatial scales, leading to the development of anthropogenic biomes (Ellis 2011; Ellis and Ramankutty 2008; Xu et al.2009). While the role of culture in traditional ecosystem management is much studied, researchers generally pay less attention to community calendars that facilitate ecosystem management. In this brief literature review, I argue that indigenous calendrical systems are powerful instruments that direct individual as well as collective actions.